Selecting a location for a liquefied natural gas terminal in the Eastern Baltic Sea - Bagočius, Vygantas; Zavadskas, Edmundas K.; Turskis, Zenonas (Transport, 2014)
Liquefied Natural Gas (LNG) industry is among the fastest growing energy market sectors. The gas terminal in Klaipėda allows Lithuania to import natural gas from various countries around the world. One of the most debatable subjects is the location of the future terminal. The problem pertaining to selection of construction sites for the LNG terminal should be investigated and solved using the set of multiple conflicting criteria. Many researchers argue that similar problems should be solved by applying several different Multi-Criteria Decision-Making (MCDM) methods. The research presents the model for application of three different MCDM methods and aggregation of solution results for the problem, which is based both on different objective data and on investigation of expert opinions for determining subjective criteria weights for the problem. First Published Online: 25 Mar 2014